Literasi Budaya Pada Anak di Rumah Pintar YAFSI “Pengolahan Sampah Plastik Menjadi Pot Bunga” - Enjelina Panjaitan, Juwita; Siregar, Hairani; Utama Ritonga, Fajar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
The rapid development of the times has made many changes in the entire scope of human life. From social behavior, technology, environment, climate and many other things. The environment is one of the things that is close to human life. The behavior towards waste has become a culture that is rooted in society. This has an impact on the mindset of the community regarding waste that is not appropriate. It takes care and concern for cleanliness in the environment. This form of concern can start from the family where there are children in it. According to R.A. Kosnan "children are young people at a young age, their souls and life journeys are easily influenced by their surroundings". In addition to environmental changes, another thing that can also be seen is the impact of parenting behavior in the field of education. There is also an increasing variety of parenting efforts for children, one of which is the application of literacy that can be started from early childhood. Literacy is a term that refers to a series of individual abilities and skills with reading, writing, speaking, calculating and solving problems in a certain level of expertise needed in everyday life. Through cultural literacy Field Work Practice is an activity related to children, literacy, and waste processing. Through the literacy of plastic waste processing, it aims to increase public awareness, and foster children's sensitivity to waste. Children also need an attitude of love for the surrounding environment. This will make people's stigma towards waste will change and start healthy living behavior and maintain the cleanliness of the living environment.